Functions Modeling Change: A Preparation for Calculus, 5th Edition

Published by Wiley
ISBN 10: 1118583191
ISBN 13: 978-1-11858-319-7

Chapter 11 - Polynomial and Rational Functions - Strengthen Your Understanding - Page 489: 3



Work Step by Step

Let $g(x)=x^p$ where $p$ is even. Therefore, $p=2j$ for some $j \in \Bbb{Z}$, meaning that $g(x)=x^{2j}$. Since $(x^a)^b=x^{ab}$, $$g(x)=(x^2)^j$$ Use $x=-1$. This gives $$g(-1)=((-1)^2)^j=1^j$$ One to any positive integer is one. Therefore, all power functions of that form pass through $(-1,1)$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.